# Extensions 1→N→G→Q→1 with N=C2×C4 and Q=C2×3- 1+2

Direct product G=N×Q with N=C2×C4 and Q=C2×3- 1+2
dρLabelID
C22×C4×3- 1+2144C2^2xC4xES-(3,1)432,402

Semidirect products G=N:Q with N=C2×C4 and Q=C2×3- 1+2
extensionφ:Q→Aut NdρLabelID
(C2×C4)⋊1(C2×3- 1+2) = C22⋊C4×3- 1+2φ: C2×3- 1+2/3- 1+2C2 ⊆ Aut C2×C472(C2xC4):1(C2xES-(3,1))432,205
(C2×C4)⋊2(C2×3- 1+2) = C2×D4×3- 1+2φ: C2×3- 1+2/3- 1+2C2 ⊆ Aut C2×C472(C2xC4):2(C2xES-(3,1))432,405
(C2×C4)⋊3(C2×3- 1+2) = C4○D4×3- 1+2φ: C2×3- 1+2/3- 1+2C2 ⊆ Aut C2×C4726(C2xC4):3(C2xES-(3,1))432,411

Non-split extensions G=N.Q with N=C2×C4 and Q=C2×3- 1+2
extensionφ:Q→Aut NdρLabelID
(C2×C4).1(C2×3- 1+2) = C4⋊C4×3- 1+2φ: C2×3- 1+2/3- 1+2C2 ⊆ Aut C2×C4144(C2xC4).1(C2xES-(3,1))432,208
(C2×C4).2(C2×3- 1+2) = M4(2)×3- 1+2φ: C2×3- 1+2/3- 1+2C2 ⊆ Aut C2×C4726(C2xC4).2(C2xES-(3,1))432,214
(C2×C4).3(C2×3- 1+2) = C2×Q8×3- 1+2φ: C2×3- 1+2/3- 1+2C2 ⊆ Aut C2×C4144(C2xC4).3(C2xES-(3,1))432,408
(C2×C4).4(C2×3- 1+2) = C42×3- 1+2central extension (φ=1)144(C2xC4).4(C2xES-(3,1))432,202
(C2×C4).5(C2×3- 1+2) = C2×C8×3- 1+2central extension (φ=1)144(C2xC4).5(C2xES-(3,1))432,211

׿
×
𝔽